Law in a Transitional Society: Discussing Emile Durkheim's Thoughts on Law and Society in an Indonesian Context - Achmad Siddiq (GoAcademica Research & Publishing, 2023)
This paper discusses Emile Durkheim's thoughts as a figure in early legal sociology studies, and their contextualization in Indonesian reality. Durkheim in his theory divides society into two types, simple and modern. Simple society is characterized by streamlined work differentiation, mechanical social solidarity, and repressive types of laws. Meanwhile, modern society is characterized by an increasingly diverse and specific division of labor, organic solidarity and restitutive legal types. In the Indonesian context, the New Order era was an era of economic development that was full of issues of industrialization, law was used as a tool of social engineering and served for practical purposes, the volume of regulations increased until there was what Susskind called hyperregulation. Another issue is the legal unification project, this project is powerless because it has to deal with local legal forces inherent in society. This kind of legal condition shows the social condition of a society that still upholds collective spirit or awareness, a characteristic of a simple society in Durkheim's perspective of thought. but on the other hand, the need for and the applicability of positive law nationally along with the development of society as well as the development of legal institutions and professions, can be used as a reflection of the characteristics of modern society in the perspective of Durkheim's thought. The two categories of law and society that Durkheim theorized were in one container, namely Indonesian law and society, a uniqueness as well as a criticism of Durkheim's theory.